Occurrence of Communal Violence and its Implication among Young People in Odukpani Local Government Area of Cross River State, Nigeria - Edet, Brian; Ndep, Antor; Offiong, Dominic; Okon, Aniekan-abasi; Akpan, Margret (dialektika kontemporer, 2025)
Introduction: The World Health Organization (WHO) defines violence as “the intentional use of physical force or power, threatened or actual, against oneself, another person, or against a group or community that either results in or has a high likelihood of resulting in injury, death, psychological harm, mal development or deprivation (Singh, & Gururaj, 2014).Aim/ objectives: This study aimed to determine the occurrence of communal violence and it's implication among young people in Odukpani Local Government Area of Cross River State, Nigeria. Methodology: It was guided by three (3) research questions and two (2) hypotheses, with the theory of ecological model supporting the study. The study employed a community-based cross-sectional study design to collect data on communal violence and it's implication among young people in Odukpani Local Government Area of Cross River State. A sample size of 300 respondents was selected using a multi-stage sampling technique. The data collection instruments included a semi-structured questionnaire. Data were analysed using Microsoft Excel 2010 and Statistical Package for Social Sciences (SPSS) software version 20. The analysis was done using cross tabulation while Pearson’s chi-square test was used for testing associations of selected variables with a significance level set at P<0.05.Results and discussion: A total of 300 respondents participated in the study giving a response rate of 100%. More than half 221(73.7%) of the respondents were males while a greater proportion 127(42.3%) fell within the age bracket 15-20years followed by those 63(21.0%) within the age bracket 21-27years. Majority 148(49.3%) had secondary education and the least 11(3.7%) had primary education. More than half 158(52.7%) of the respondents were students, followed by those 31(10.3%) who were traders and the least 18(6.0%) were farmers. Majority 273(15.99%) reported that harmful use of drugs is a major reason young people engage in violence followed by 250(14.65%) who reported easy access to guns and fire-arms.Conclusion and recommendation: Communal violence is prevalent in the three communities in Odukpani Local Government Area. Tussle for land and chieftaincy has been the major determinants of communal violence. Preventive measures ranges from withdrawal of arms from people, implementing government laws against violence and designing youth programmes against violence.